Enhancing Islamic Millennial Students' Writing Skills through Facebook Class - Azza Jauhar Ahmad Tajuddin; Hesty Puspita Sari; Imroatul Hasanah; Mauhibur Rokhman; Ahmad Saifudin; Latifatul Isro’iyah; Mohammad Maulana Nur Kholis (Universitas Pesantren Kh abdul Chalim Mojokerto, 2025)
The Islamic millennial generation was born in 1980-2000 and is very familiar with technology, so were Ushuluddin students of IAIN Kediri in the first semester of the 2022/2023 academic year. For their interest in improving their English writing skills, the researcher used a different class named Facebook class. Students had to upload their writing works on their Facebook tagging the researcher and their friends in the class. The research was to improve the writing skills of Ushuluddin students using the Classroom Action Research Method. It was conducted at IAIN Kediri and involved 220 Ushuluddin student’s faculty, as the object of the research. The participants were spread in 6 classes in 4 study programs. The result showed that students' marks increased, and so was their motivation to write. This implied that the Facebook class was a good way to learn writing. Then it can be concluded that students' writing skill was improved using Facebook class. Lecturers are very suggested to take the benefit of Facebook for the writing learning process.